Concerns about the Euro and happiness in Germany during times of crisis - Adrian Chadi (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2015)
This empirical study investigates if people's concerns about the euro currency affect their life satisfaction. A minority of very concerned individuals appear to be unhappy, which cannot be explained by personality or other observable factors typically affecting well-being. As a novelty, this investigation exploits exogenous variation in reported concerns by using the intensity of media coverage on the euro crisis with its extraordinary events throughout the year 2011 as an instrument. Results from the application of several empirical approaches confirm that there is an effect from being concerned about the euro on people's satisfaction with life. The first potential explanation is that perceived economic insecurity works as a transmission channel, but this is not fully supported by the empirical evidence. A second explanation suggests that political beliefs and euro-skeptic attitudes are at play and may trigger unhappiness as a consequence of a perceived lack of representation in German politics. In line with this argument, a regional analysis links the variation in unhappiness among concerned citizens to the actual votes for Germany's first major anti-euro party in the subsequent federal elections.
Keywords: D72; H11; I31; 330; life satisfaction; euro crisis; currency; concerns; political protest; sensitive information; media coverage; instrumental variable; SOEP